2023
DOI: 10.1038/s42003-023-04967-z
|View full text |Cite
|
Sign up to set email alerts
|

Century-long butterfly range expansions in northern Europe depend on climate, land use and species traits

Abstract: Climate change is an important driver of range shifts and community composition changes. Still, little is known about how the responses are influenced by the combination of land use, species interactions and species traits. We integrate climate and distributional data for 131 butterfly species in Sweden and Finland and show that cumulative species richness has increased with increasing temperature over the past 120 years. Average provincial species richness increased by 64% (range 15–229%), from 46 to 70. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 98 publications
2
12
0
Order By: Relevance
“…Ecological traits are an important driver of variability in the slope and direction of abundance and distribution trends, with positive trends often associated with traits such as high mobility, wide host ranges, ecological generalization, broad thermal tolerance and large geographical ranges [5][6][7][8][9]. This combination of ecological attributes is generally considered to be part of the insect such as pollination [15,16] and biological control [17,18], it is increasingly important to monitor movement patterns, phenology and abundance of migratory insects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecological traits are an important driver of variability in the slope and direction of abundance and distribution trends, with positive trends often associated with traits such as high mobility, wide host ranges, ecological generalization, broad thermal tolerance and large geographical ranges [5][6][7][8][9]. This combination of ecological attributes is generally considered to be part of the insect such as pollination [15,16] and biological control [17,18], it is increasingly important to monitor movement patterns, phenology and abundance of migratory insects.…”
Section: Introductionmentioning
confidence: 99%
“…habitat loss and fragmentation, urbanization, pollution and climate change, in driving the potential crisis in insect communities. By contrast, some studies have demonstrated that population trends are more complex and nuanced, with a mix of decreasing, stable and increasing abundance and distribution trends, often co-occurring in the same insect communities [ 3 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, only rigorous assessments of annual migration phenology enable the detection of shifts in mean migration counts which may be attributable to phenomena such as global warming (Cotton, 2003; Taylor, 2008). These shifts could potentially be associated with range shifts in butterflies (Parmesan et al, 1999; Sunde et al, 2023) which could, in turn, manifest as changes in orientation behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Human influence and climate change are driving substantial changes in the species compositions of habitats and ecosystems [ 1 , 2 , 3 ]. Understanding the biodiversity of complex and rich insect communities is an essential cornerstone of ecological research [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current environmental changes impose intense pressure on species, especially those with narrow and specific ecological requirements, leading to decreased population sizes, shrinking distribution ranges, and increased extinction rates [ 9 , 10 , 11 ]. In contrast, generalist species, characterised by broader ecological tolerance, demonstrate remarkable resilience by being able to exploit available resources and adapt their phenology and geographical range to suit the present circumstances [ 1 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%